Comprehensive mental health and psychosocial support case management and indicative care pathways within humanitarian settings. Issue 3 (November 2016) - Quosh, Constanze
Abstract : This article describes the approach, implementation and evaluation of a pilot mental health and psychosocial support case management programme that was developed by the United Nations High Commissioner for Refugees in Syria. The aim was to provide a description of the programme approach, its implementation and outputs. The programme integrates different forms of case management approaches based on a multi-layered, stepped care model. Earlier results of mixed method monitoring and evaluation revealed improvement in wellbeing among programme participants. The step-wise approach indicates, in addition to the positive mental health outcome results, a functional case management system.